Imaginarios sociales y conflictos en las expresiones de la música vallenata y la champeta en el Caribe colombiano (2021)
This reflection article, resulting from a strict research project, allowed to make an analysis of the discursive approach that frames the birth and development of champeta and vallenato music in the populations where they are representative (the cities Cartagena and Valledupar respectively) from a sociological perspective. In addition, it enabled to understand the existing relationship between the musical expressions of these genres, taking into account both the social imagery associated with each one, as well as, the understanding of the different social factors associated with their representations.